Rare bird documentation form for Northern Goshawk at Sweet Marsh, 1998 - Moore, Francis L.et al (1998)
Rare bird documentation form for a Northern Goshawk at Sweet Marsh in Bremer County, IA on December 19, 1998. Epson - sheet feed